Pengaruh Penempatan Kerja Dan Beban Kerja Terhadap Kinerja Pegawai Melalui Kompetensi Sebagai Variabel Intervening Pada Dinas PUPR Pemerintahan Provinsi Sumatera Utara - Ramdhana, Farhan; Astuti, Rini (JURNAL MANAJEMEN DAN BISNIS, 2025)
Purpose - This study aims to analyze the effect of job placement and workload on employee performance through competence as a mediating variable in the Water Resources Division of the North Sumatra Provincial PUPR Department. Novelty - Most previous studies have not analyzed the mediating role of competence in the relationship between job placement and workload and their impact on employee performance in government institutions, particularly under real conditions where placement mismatches affect performance variation. Method - This research adopts a quantitative method with a causal associative approach involving 59 employees using a total sampling technique. Data were collected through interviews, documentation, and Likert scale questionnaires, and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0. Findings - The results show that job placement has a positive and significant effect on both competence (t = 3.386) and employee performance (t = 2.619). Workload also has a positive and significant effect on competence (t = 2.810) and employee performance (t = 2.118). Furthermore, competence has a positive and significant effect on performance (t = 2.930) and effectively mediates the influence of both job placement and workload on employee performance, either partially or simultaneously, with an R-Square value of 0.883 (88.3%). Limitations and Implications - This study is limited to a single division with a small sample size and a cross-sectional approach. However, it offers practical implications for designing job placement systems based on educational alignment and managing proportional workloads to optimize employee performance through competence development.